Transparency in governance through right to information - Tolia, R. S. (Dehradun, 2010)
The book is a tell all, from the man behind the empowerment through RTI of the hill state of Uttarakhand. It is a story of unending hard work and enthusiasm, of positivity and insightful vision. This book reveals how RTI is a powerful tool in bringing accountability and transparency in governance in India.
Keywords: Right to information